ApoA-IMilano phospholipid complex (ETC-216) infusion in human volunteers. Insights into the phenotypic characteristics of ApoA-IMilano carriers. (September 2016) - Bisgaier, Charles L.; Ackermann, Rose; Rea, Thomas; Rodrigueza, Wendi V.; Hartman, Daniel
Abstract: Epidemiological studies support an inverse correlation between HDL-C and cardiovascular disease. However, low HDL-C levels do not always segregate with premature disease. These include, LCAT deficiency and the apolipoproteinA-IMilano (AIM) variant. AIM has a cysteine for arginine at position 173 in the otherwise cysteine free protein permitting AIM homodimerization and apoA-II heterodimerization. We relate the biochemical characteristics of low HDL-C phenotype AIM carriers to lipoprotein changes in humans administered recombinant dimeric AIM/palmitoyl-oleoyl phosphatidyl choline (ETC-216). Pharmacokinetic analysis of infused ETC-216 suggest a slow distribution of AIM into peripheral tissue and an extremely long terminal half-life in plasma. Following ETC-216 administration to normal human volunteers, an initial dose-dependent HDL-C elevation was observed. Thereafter, subjects transiently acquired a lipoprotein profile similar to that of AIM carriers, including reduced HDL-C and mild hypertriglyceridemia. The time-dependent changes in plasma lipids/lipoproteins may support an increased tissue cholesterol removing capacity of ETC-216. These findings provide mechanistic insight into the rapid removal of atheromatous plaques observed in humans, possibly linked to enhanced cholesterol removal capacity of ETC-216.